Success Rate of Hysteroscopy and Endometrial Scratching in Repeated Implantation Failure: A Randomized Controlled Clinical Trial: - Sarrafzadeh, Yasaman; Zahiri, Ziba; Kazem Nejad Leili, Ehsan; Sheibani, Alireza (Galen Medical Journal, 2021)
Background: Endometrial receptivity is one of the most important factors in vitro fertilization (IVF) success rate. Many different methods have been suggested to enhance the rate of implantation in IVF\ intracytoplasmic sperm injection (ICSI) cycles. Endometrial injury, as an intentional trauma aimed at improving the fertility results, has gained significant popularity among women seeking pregnancy. This study was conducted to determine the success rate of hysteroscopy and scratching before microinjection in cases of repeated implantation failure. Materials and Methods: This prospective, randomized controlled trial consist of 228 women who were referred to the Al-Zahra Infertility clinic for fertility treatment with the history of failure in at least two ICSI cycles. The patients were divided into two groups. The first group was treated by hysteroscopy without intervention, while the second group underwent hysteroscopy and scratching in the luteal phase of the menstrual cycle prior to microinjection cycle. The controlled ovarian stimulation (COS) was performed in all patients using the antagonist method. The success was considered based on the observation of the fetal heart activity in ultrasound. Results: The success rate of hysteroscopy and scratching (41.5%) was higher compared to hysteroscopy alone (34.3%), but this difference was not statistically significant based on the Chi-square test (P=0.280). The rate of miscarriage in hysteroscopy plus scratching and hysteroscopy alone were 5.7% and 12.4%, respectively which were not statistically different (P=888). Furthermore, the effect of hysteroscopy and scratching on visualizing the fetal heart activity was not statistically different compared to hysteroscopy alone (P=0.223). Conclusion: The results showed that the success rate in hysteroscopy plus endometrial scratching was not significantly different from hysteroscopy alone. [GMJ.2021;10:e1399]